Case Report: Primary leiomyosarcoma of the breast - Lv, Haoqiang; Ren, Haiyang; Zhang, Shuang; Ding, Gen; Tian, Ping (Frontiers in Oncology, 2025)
Primary leiomyosarcoma of the breast is an extremely rare tumor originating from the mesenchymal tissue of the breast. The clinical data of a case of primary leiomyosarcoma of the breast admitted to our hospital on September 11, 2024 were analyzed. A 58-year-old woman had a right breast mass for a week. Physical examination revealed an irregular mass at approximately 2–3 points in the right upper quadrant of the breast. Laboratory tests showed normal results for the tumor marker CA153. Color Doppler ultrasound considered solid nodules (BI-RADS Class 4b). Modified radical mastectomy and tertiary axillary lymph node dissection was performed on 2024-9-13, and the patient underwent adjuvant chemotherapy after surgery and recovered well. Pathological findings were reported one week after surgery: breast leiomyosarcoma. This article presents the diagnosis and treatment of primary leiomyosarcoma of breast through a clinical case, which provides a reference for clinicians. This case highlights the importance of pathological examination in the diagnosis of rare tumors, and suggests the need to combine imaging, laboratory examination and pathological findings to make a comprehensive judgment of breast masses.